BIO-ELECTROCHEMICAL MODELING ON EFFECT OF SUBSTRATE INITIAL PH ON THE PERFORMANCE OF MICROBIAL FUEL CELL (MFC) - Tri Uzila, Agi
MFC is a very profitable source of renewable energy because it uses waste to generate electricity. Several factors can affect the performance of MFCs. One of them is the initial pH of the substrate. Laboratory experiments to investigate the influence of these factors on MFC performance are often hampered due to several factors, such as cost, materials, design, and bioelectrochemical aspects. Therefore, mathematical modeling of MFC is a good option because it can overcome these obstacles. In this study, bioelectrochemical modeling was carried out to predict the effect of substrate initial pH on electricity production and microbial growth in MFCs. The methodology consist of literature study, model development, determination of modeling parameters, simulation, model validation, and analysis. Modeling was carried out under both dynamic and steady conditions for a two-chamber batch MFC. Dynamic modeling generates biofilm formation profile and OCV curve, while steady modeling generates IVP curve. Dynamic modeling results verify that the initial pH value of substrate affects the formation of biofilm and OCV value of MFC. Based The higher the initial pH value from neutral condition reduces the microbial growth rate, hence the biofilm formation and OCV value decreased. The highest OCV value at 0.95 V was obtained in MFC with an initial pH of 8. Biofilm formation at initial pH value of 7 was the fastest to stationary phase. From the steady-state simulation, the initial pH value of the substrate affects the voltage and power density produced by the MFC. The highest voltage and power density of MFC was obtained at pH 7, which was 0.77 V and 0.0055 W/m2. The optimum initial pH value of the substrate generates the highest current density and voltage, resulting in maximum power output of MFC.